ESX‐1‐induced apoptosis is involved in cell‐to‐cell spread of Mycobacterium tuberculosis - Aguilo, J. I.; Alonso, H.; Uranga, S.; Marinova, D.; Arbués, A.; Martino, A.; Anel, A.; Monzon, M.; Badiola, J.; Pardo, J.; Brosch, Roland; Martin, Carlos (Cellular microbiology, 2013)
Summary Apoptosis modulation is a procedure amply utilized by intracellular pathogens to favour the outcome of the infection. Nevertheless, the role of apoptosis during infection with Mycobacterium tuberculosis, the causative agent of human tuberculosis, is subject of an intense debate and still remains unclear. In this work, we describe that apoptosis induction in host cells is clearly restricted to virulent M. tuberculosis strains, and is associated with the capacity of the mycobacteria to secrete the 6 kDa early secreted antigenic target ESAT‐6 bothunder in vitro and in vivo conditions. Remarkably, only apoptosis‐inducing strains are able to propagate infection into new cells, suggesting that apoptosis is used by M. tuberculosis as a colonization mechanism. Finally, we demonstrate that in vitro modulation of apoptosis affects mycobacterial cell‐to‐cell spread capacity, establishing an unambiguous relationship between apoptosis and propagation of M. tuberculosis. Our data further indicate that BCG and MTBVAC vaccines are inefficient in inducing apoptosis and colonizing new cells, correlating with the strong attenuation profile of these strains previously observed in vitro and in vivo.